MEMORIES OF MIROSŁAWA GAZIŃSKA - Markowicz, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-bidi-font-weight: bold; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">MEMORIES OF MIROSŁAWA GAZIŃSKA